Analysis Of Altman Z-Score Modified Methods in Predicting Bankruptcy in LQ45 Companies - Ifanda Maya Arista; Mochamad Kohar Mudzakar (Majalah Bisnis & IPTEK, 2022)
The purpose of the study was to predict bankruptcy rates in companies indexed in LQ45. The study was conducted on 20 companies as samples taken based on purposive sampling techniques for the period 2019 – 2021. The research method used is explanatory with descriptive investigations. The results showed that companies that met the healthy category in 2019, 15 companies, in 2020, 13 companies, and in 2021, 14 companies. Grey area category in 2019 – 2020, 3 companies, in 2021, 2 companies. For the bankruptcy category in 2019, 2 companies, and in 2020 – 2021, 4 companies.